Impact of OXTR Polymorphisms on Subjective Well-Being: The Intermediary Role of Attributional Style - Ji, Lei; Chen, Changfeng; Hou, Binyin; Ren, Decheng; Yuan, Fan; Liu, Liangjie; Bi, Yan; Guo, Zhenming; Yang, Fengping; Wu, Xi; Chen, Fujun; Li, Xingwang; et al. (Frontiers in Genetics, 2022)
Polymorphisms in the oxytocin receptor (OXTR) gene have been shown to be related to individual differences in negative emotions, such as depressive symptoms and anxiety. However, it remains unclear what the potential roles of OXTR polymorphisms are in subjective well-being (SWB), which is negatively correlated with depressive symptoms. We examined attributional styles as mediator between SWB and five polymorphisms of the oxytocin receptor gene (OXTR rs53576, rs2254298, rs1042778, rs2268494, and rs2268490) among 627 full-time college freshmen (Mage = 20.90, SD = 0.82 for male; Mage = 20.81, SD = 0.92 for female) using structural equation modeling. The results showed that individuals with the OXTR rs2254298 AA genotype and rs53576 AA/GA genotype reported higher scores on SWB, which suggested that individuals with this genotype experienced more happiness. Moreover, external attributional style partially mediated the association between OXTR rs2254298 polymorphism and SWB (β = 0.019, 95%CI [0.001, 0.036], P = 0.035). In conclusion, our findings demonstrated that the genetic variations of OXTR played a role in the individual differences of SWB and external attribution style could mediate the association.